(3GQJTGa GdVQH ef dSGf GdYQHs - (3eMeO Hf jhSa Hf Ydj Hf jhSa GHf nMnqjGf GdZQfGWj GdCfOdSj GdLjGfj, GdpqfraRj, CKjQ GdOjf, CHh MjGf,J (B745 (3g` s ((3eMeO Hf CMeO s)
(3ChdgG (B:s
(3JHJOj HHGH GdefUhHGJ, HGH GdeaYhd GdeWdb bhdg(B: (3hHbi GdcdGe Ydi HGbj GdefUhHGJ s
(3BNQgG (B:s
(3adh bOeJ RjOkG Ydi VQH ZdGeg efYgG GdcSGFj hGdaQGA hCLGRgG hGdeHQO s
(3fSNI NGeSIs
(3JJab aj BNQgG eY BNQ GdfSNI GdChdi hHChdgG Jedc GdYdGeI eMeO GdUZjQ Hf eMeO Hf CHj HcQ GdOdGFj hagQS dCHhGH GdcJGHs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B152 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B130s
Keywords: (3GdfMhs